Peningkatan keterampilan membaca dengan media cerita gambar pada pelajaran PPKn dikelas II MI NW Penakak - Muh. Bisyrulhafy; Wawan mulyadi Purnama; Royani (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to improve the reading skills of elementary school (SD/MI) students by using picture story media, so that students become more enthusiastic about reading. This research uses classroom action research (PTK) which consists of four stages passed in each cycle. The purpose of classroom action research is to improve and refine classroom learning practices. The model used in this research is the Kemmis & Taggart model, which essentially consists of a device or a series of devices with one device consisting of one component: planning, action, observation, and reflection. The results showed that there was an improvement in reading skills through the use of picture story media structure in class II MI NW Penakak. As the research results indicated, in cycle I as many as 11 students out of 23 students achieved mastery, with a classical mastery percentage of 60.34%. In cycle II, as many as 15 students out of 23 students reached mastery with a classical mastery percentage of 87.65%. Therefore, the researcher concludes that the use of picture story media structure in improving students' reading skills in the PKn subject with the theme of Pancasila values in daily life in class II MI NW Penakak can be said to be successful.